Estimativa de perdas econômicas e produtivas do estresse por calor e efeito de ondas de calor sobre o desempenho de frangos de corte em ambiente tropical - Moraes, Cíntia Amaral (2020)
Climate change is considered a challenge in broiler breeding. In this context, knowing the incidence of heat waves and their effects on the performance of chickens is essential in choosing the type of air conditioning used in the aviary that guarantees the expression of genetic potential and animal welfare.Thus, in the first study, the objective was to perform bioclimatic zoning, the estimate of economic and financial losses caused by heat stress in a tropical environment. For this, the daily maximum, minimum and average daily temperature and humidity index (THI) was calculated in eight weather stations from 2002 to 2019, duration of the thermal heat accumulated in one day (THI Load), duration of the stress period (D), reduction in the consumption of poultry feed under heat stress (DMI Loss), loss of weight gain (Gain Loss), variation in the mortality rate due to thermal stress (PDeath) and later production costs and estimates of financial losses because of heat stress. May to August were characterized by lower risks of thermal discomfort for the production of broilers in Araxá, Patrocínio, Conceição das Alagoas, Sacramento, Uberaba and Uberlândia and from September to April there was a need to use an artificial thermal conditioning system to minimize variations in the thermal environment in all cities studied. Performance was impaired when no cooling techniques were used. The Ituiutaba and Campina Verde regions are unfavorable places for the rearing of broilers, for zootechnical and financial indicators. In the second study, the objective was to evaluate the effects of heat waves on the performance of broiler chickens raised in semi-climatic and climatic sheds and the mortality rate during transport to the slaughterhouse. In this way, the daily weight gain, slaughter weight and mortality rate of “griller” chickens reared in semi-climatic and acclimatized sheds were calculated, in addition to the mortality rate during transport to the slaughterhouse. The poultry cooling system (semi-climatic and acclimatized) did not interfere with daily weight gain and slaughter weight, but the mortality rate was higher in broilers raised in a semi-climatic system compared to those raised in a climatized system. In the semi-climatic house, the lowest mortality rate occurred in wave types I, III and IV in relation to type II, however type II did not differ from I and IV. The mortality rate during transport to the slaughterhouse increased with the addition of THImax. Heat waves lasting 10 days or more do not affect slaughter weight and daily weight gain of broilers raised in a semi-climatic system and in a climatized system in a tropical environment, however, the mortality rate of birds in semi-climatic sheds increases with the increase of heat wave days. The mortality rate during transport to the slaughterhouse increases with the addition of THImax.